ARCA BHAIRAWA PADA MASA KERAJAAN DHARMASRAYA “Sejarah, Ikonografi dan Fungsi” - Arnisyah Srimayu, Drs. Ady Rosa, M.Sn, Ir. Drs. Heldi. M.Si (Serupa The Journal of Art Education, 2013)
The purpose of this research is to know about: history, iconography and function Bhairava statue in the kingdom of Dharmasraya. Type of research is descriptive qualitative. Data source is where the data subject is obtained, (1) at the museum replica statue of Bhairava Adityawarman Padang, (2) where is placed the statue of Bhairava the National Museum in Jakarta. (3) place of found that is in Dharmasraya Bhairava statue. The data source is the data obtained through interviews and written documents search. Analysis data collection in accordance with the descriptive data processing techniques, describes the phenomenon as it is written in narrative form, which was obtained through field observations undertaken in Bhairava statue. Kata kunci: Sejarah, Ikonografi, Fungsi